1977
DOI: 10.1099/00221287-102-1-111
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification Studies at Non-limiting Substrate Concentrations

Abstract: I 1 1Theoretical models of nitrification were tested using an experimental model consisting of a column of glass beads inoculated with nitrifying bacteria, through which was passed a constant flow of substrate at non-limitingconcentration. Effluent was analysed for conversion products.Both zero-order and first-order rate constants for substrate conversion decreased by 1.4 % for each I ml h-l decrease in flow rate presumably because of the development of oxygen limitation. Logistic growth kinetics described gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The ratio reported by Prosser and Gray [35] is 1/100, but the activity of the Nitrobacter sp. they used is 10 times lower than the mean activities reported by Prosser [36].…”
Section: Biomass Distribution In Steady-statementioning
confidence: 93%
See 1 more Smart Citation
“…The ratio reported by Prosser and Gray [35] is 1/100, but the activity of the Nitrobacter sp. they used is 10 times lower than the mean activities reported by Prosser [36].…”
Section: Biomass Distribution In Steady-statementioning
confidence: 93%
“…This can be compared with the observation of Cox et al [17] who found that less than 20% of their column was active in their non-limiting working conditions. The development of Nitrosomonas in the lower part of a ®xed bed column packed with glass bead is reported too by Prosser and Gray [35], together with a rather homogenous distribution of Nitrobacter in the same column.…”
Section: Biomass Distribution In Steady-statementioning
confidence: 94%